Enhancing Mass Casualty Disaster Management Competencies through an Integrated Disaster Simulation Training Program. (August 2022) - Gundran, Carlos Primero D.; Lam, Hilton Y.; Tuazon, Anna Cristina A.; Cleofas, Jerome V.; Garcia, Fernando B.; Puli, Trisha Ericka M.; Magdales, Ma Sarina I.
Abstract: The Center for Innovations for Disaster Risk Reduction and Management in Health (DRRM-H) in NCR program developed a disaster simulation training aimed to address the challenges in communication, collaboration, and application of incident command system (ICS) during disaster response. This study aims to identify the effectiveness of an integrated didactic and simulation learning approach to disaster training using quantitative and qualitative methods. Results of the study indicate that training participants were able to increase their knowledge on the concepts of communication, collaboration, and application of ICS, and adopt these lessons to their own organizations to increase their capacity and capability during disaster response.